Psychogenic fever and neurodevelopmental disorders among Japanese children - Ayumi Okada; Yoshie Shigeyasu; Chikako Fujii; Chie Tanaka; Mana Hanzawa; Akiko Sugihara; Makiko Horiuchi; Hirokazu Tsukahara (BioPsychoSocial Medicine)
Abstract Background Psychosocial stress can induce various physical symptoms, including fever, which is a commonly seen symptom in pediatric practice. In cases of unexplained fever, psychogenic fever should be considered as a potential cause. Children with neurodevelopmental disorders may be more vulnerable to stress and therefore more prone to developing somatic symptoms than their peers. This study aimed to elucidate the characteristics of children with psychogenic fever and comorbidity. Methods This study included 21 patients with psychogenic fever who visited the Department of Pediatric Psychosomatic Medicine, Okayama University Hospital. Information on age, sex, disease onset, final estimated diagnosis, comorbidities, treatment course, and outcome was obtained from the patients’ medical records. Results Of the 21 patients included, 7 were boys and 14 were girls, and their median age was 13.0 (range: 8.6–14.6) years. A total of 19 patients had no attendance at school, and all patients showed signs of maladjustment in school. The comorbidities included orthostatic dysregulation (n = 4) and migraine (n = 3). Neurodevelopmental disorders were observed in nine patients, eight of whom were diagnosed after the initial visit. The mean treatment duration was 37.2 months. The outcomes were complete remission (n = 9), improvement (n = 4), discontinuation (n = 1), and referral to another physician (n = 7). Conclusion Various comorbidities were observed in the patients of this study with psychogenic fever, including the coexistence of neurodevelopmental disorders, such as autistic spectrum disorder. Children with neurodevelopmental disorders are prone to psychological stress resulting from difficulties in social adjustment. It is crucial to understand the developmental characteristics and environmental adaptation of patients to facilitate accurate diagnosis and treatment.